2016
DOI: 10.1016/j.rbmo.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Semen characteristics in consecutive ejaculates with short abstinence in subfertile males

Abstract: This study reports the favourable semen characteristics of 73 subfertile oligozoospermic men with short abstinence periods up to 40 min. Semen characteristics were compared between initial and consecutive ejaculate showing improved semen parameters: progressive grade A spermatozoa, morphology and sperm concentration. Median concentrations in initial and consecutive ejaculates were 10 million/ml and 17 million/ml, respectively. The second sample had a higher median normal morphology (7% versus 6%, P < 0.001). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 32 publications
5
47
0
4
Order By: Relevance
“…A short period of abstinence could result in a "younger" population of spermatozoa that have a lower period of exposure to the toxic effects of reactive oxygen species (ROS) [22]. The improvement may also depend on the increase in the total antioxidant capacity (TAC) of semen and lower sperm membrane lipid peroxidation (LPO), as recently reported [9,23,24]. This hypothesis is further supported by the decrease in the percentage of spermatozoa with fragmented DNA in semen samples collected after shorter abstinence periods [17,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A short period of abstinence could result in a "younger" population of spermatozoa that have a lower period of exposure to the toxic effects of reactive oxygen species (ROS) [22]. The improvement may also depend on the increase in the total antioxidant capacity (TAC) of semen and lower sperm membrane lipid peroxidation (LPO), as recently reported [9,23,24]. This hypothesis is further supported by the decrease in the percentage of spermatozoa with fragmented DNA in semen samples collected after shorter abstinence periods [17,25].…”
Section: Discussionmentioning
confidence: 99%
“…In an assisted reproductive technique (ART) setting, the fertilization rate of spermatozoa obtained from a second ejaculate was significantly higher compared with that derived from the first one, suggesting that sequential ejaculations might be useful for treatment of male infertility [8]. More recently, Bahadur and colleagues clearly showed that the "median progressive motility as benchmarked by the WHO 2010 criteria were significantly higher in the second consecutive sample (43% vs. 25%, p < 0.001)" in subfertile oligozoospermic patients [9]. Alipour and colleagues showed not only higher percentages of progressive motile spermatozoa but also an improvement in sperm kinematic parameters after 2 h of abstinence compared with samples obtained after 4-7 days of abstinence [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested extremely short EA lengths (i.e. <1–4 h) due to their positive influence on semen parameters (Gosalvez et al ., ; Valsa et al ., ; Bahadur et al ., ; Mayorga‐Torres et al ., ; Ayad et al ., ). A recent systematic review of 28 studies suggested that longer EA is associated with increased semen volume and sperm count, which is also in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the abstinence time for SA as advised by WHO (2–7 days) is used by many laboratories also for IUI (Table ). The WHO does, however, not give recommendations on this aspect for IUI, and shorter intervals are probably more effective for this treatment (Levitas et al ., , ; Bahadur et al ., ). The same is true for semen collection at home.…”
Section: Discussion With Conclusionmentioning
confidence: 97%